Molecular identification of antibiotic-resistant and virulent Escherichia coli and Staphylococcus aureus isolated from dogs in Southern Benin - Ayaovi Bruno Yaovi; Arpita Das; Rama N. Behera; Prudencio Comlan Sossa-Minou; Vinod Singh Bisht; Mónica Yadav; Ayushi Kapoor; Francois Dossa; Paulin Azokpota; Souaïbou Farougou; Lamine Baba-Moussa; Kiran Ambatipudi; et al. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: Antibiotic resistance is a worldwide health challenge. Close interaction with dogs carrying antibiotic-resistant zoonotic agents poses a risk to human health. The present study aimed to characterize antibiotic-resistant Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) isolated from dogs in Southern Benin. Materials and methods: A total of 336 swabs (112 buccal, 112 nasal, and 112 rectal) from 112 dogs living in the communes of Abomey-Calavi and Cotonou were analyzed for E. coli and S. aureus presence. Bacterial isolates were tested for antibiotic (penicillins, tetracyclines, aminoglycosides, cephalosporins, sulfonamides, and macrolides) susceptibility using the disc diffusion method, and antibiotic-resistant strains were characterized by the polymerase chain reaction method. Results: A 41.07% and 20.53% of dogs harbored E. coli and S. aureus, respectively. Escherichia coli and S. aureus isolates showed resistance to penicillin (100% and 81.48%), tetracycline (44.64% and 59.26%), and other antimicrobials tested. Escherichia coli isolates harbored resistance genes blaTEM (63.46%), tetA (62.50%), and strA-strB (55.56%). tetK (100%), tetM (100%), and blaZ (82.61%) were present in S. aureus isolates. Escherichia coli strains harbored virulence genes fimH (61.54%), kpsMTII (26.92%), fyuA (19.23%), and eae (1.92%), whereas 20.83% of S. aureus strains harbored pvl and fnbA. Conclusion: The results of the current study reveal the urgent need for stricter controls on antibiotic use. Implementing guidelines, responsible prescribing, and increasing public awareness are crucial steps to address this problem. [J Adv Vet Anim Res 2025; 12(2.000): 396-419]